Co-planar microwave integrated circuit transmission lines based on carbon nanotube and graphene / Mohsen H S Ben Kara - H S Ben Kara, Mohsen (Institute of Graduate Studies, UiTM, 2016)
The aim of this work is to study the feasibility of using carbon nanotube and graphene as new conductor materials for microwave integrated circuits (MMIC). As the dimensions of integrated circuits scale down to nanometers, the conductor resistance at high frequencies increase due to skin effect, and consequently the performance of MMICs degrade. Nanomaterials based on carbon are therefore proposed in this study as new material for MMIC due to their promising electrical properties including high mobility, high current densities, and negligible skin effect. Co-planar transmission lines were built from carbon nano-tube (CNT) and graphene using techniques compatible with semiconductor processing. In this work CNT was grown on Ni-coated Si wafers using a modified thermal CVD method, the Ni acting as growth catalyst. The optimal conditions were 900 °C reaction temperature, 4 nm catalyst thickness and 100 bubbles/min. gas flow rate. In addition, graphene was etched using a modified process which offer layer-by-layer etch, thus offering easy process control. The physical properties of both CNT and graphene films were analyzed using optical, SEM, FESEM and EDS for microstructure analysis, and Raman spectroscopy for crystalline analysis…